Fish species of fishermens’ catches in Kuala Tungkal - Tungkal Ilir Sub-District, Tanjung Jabung Barat Regency, Jambi Province - Khaerudin Khaerudin; Afreni Hamidah; Winda Dwi Kartika (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2018)
The aim of this study was identify fish species caught by fishermen in the fish auction site (FAS) and compare with fish species in the fish market of Kuala Tungkal, Tanjung Jabung Barat Regency, Jambi. Fish samples were collected from FAS and fish market of Kuala Tungkal from July to August 2014. Fish identification was done according to morphome-tric characteristics of fish speciemens using fish identification books. A total of 49 fish species belonging to 32 families and 11 orders were identified along the study period. The number of fish species found in TPI and fish markets was dif-ferent. Thirty-two fish species were recognized in FSA and 13 species of which were not found in the fish market. Of the 36 fish species found in the fish market, 17 fish were not collected in the FSA. A total of 19 fish species fish were found in both locations. It is necessary to conduct a similar research in different seasons to obtain a comprehensive in-formation about fish species caught in the waters around Tanjung Jabung Barat, Jambi.uct research in a longer period of time. Thus it is hoped that more fish species may be found only in certainseasons. Abstrak Penelitian ini bertujuan untuk mengidentifikasi jenis-jenis ikan yang tertangkap oleh nelayan dan dilelang di Tempat Pelelangan Ikan (TPI) serta membandingkannya dengan hasil tangkapan nelayan yang ada di pasar ikan Kuala Tungkal. Sampel ikan diambil dari hasil tangkapan nelayan yang akan dilelang di TPI dan pasar ikan Kuala Tungka dari Juli sampai Agustus 2014. Proses identifikasi dilakukan dengan membandingkan karakteristik morfologi spesimen dengan menggunakan buku identifikasi ikan. Teridentifikasi sebanyak 49 jenis ikan dari 32 famili dan 12 ordo selama peneli-tian. Ada perbedaan jumlah jenis ikan yang dikoleksi antara TPI dengan pasar ikan. Sebanyak 32 spesies ikan teriden-tifikasi di TPI dan 13 spesies diantaranya tidak ditemukan di pasar ikan. Dari 36 spesies ikan yang ditemukan di pasar ikan, 17 ikan tidak ditemukan di TPI. Sebanyak 19 jenis ikan ditemukan di kedua lokasi. Perlu dilakukan penelitian serupa pada musim yang berbeda untuk mendapatkan informasi yang utuh mengenai jenis-jenis ikan yang tertangkap di perairan sekitar Tanjung Jabung Barat, Jambi.